Impact of KIT mutation on efficacy of venetoclax and hypomethylating agents in newly diagnosed acute myeloid leukemia - Wenxiu Shu; Qianqian Yang; Donghua He; Yi Li; Jing Le; Qianqian Cai; Hui Dai; Liufei Luo; Bingrong Chen; Yuan Gong; Dian Jin (European Journal of Medical Research)
Abstract Background The combination of venetoclax (VEN) with hypomethylating agents (HMAs) has emerged as a new standard treatment for older or unfit patients with acute myeloid leukemia (AML). However, the predictive factors for VEN/HMA efficacy remain unclear. In our study, we performed the first analysis of the impact of KIT mutations on therapeutic outcomes in newly diagnosed AML patients undergoing VEN/HMA regimens. Methods In this retrospective study, we included 16 KIT-mutant AML patients receiving VEN/HMA (Cohort A), 141 KIT-wild-type AML patients receiving VEN/HMA (Cohort B), and 69 KIT-mutant AML patients receiving intensive chemotherapy (IC) (Cohort C). We compared the differences in therapeutic efficacy among the different cohorts. Furthermore, we conducted multivariate analyses in patients receiving VEN/HMA to identify factors influencing therapeutic outcomes. Results Compared to Cohort B, Cohort A exhibited significantly lower overall response rate (ORR) (18.8% vs. 72.3%, p < 0.001) and measurable residual disease (MRD) negativity rate (18.8% vs. 68.1%, p < 0.001), with a shorter median event-free survival (EFS) (1.9 months vs. 7.8 months, p < 0.001). No significant difference in overall survival (OS) was observed. Among KIT-mutant patients, IC showed superior ORR (78.3% vs. 18.8%, p < 0.001), MRD negativity rate (75.4% vs. 18.8%, p < 0.001), and EFS (12.2 months vs. 1.9 months, p < 0.001) compared to VEN/HMA. No significant difference in OS was observed between the two cohorts. Multivariate analysis confirmed KIT mutations as an independent predictor of lower ORR (OR 0.020, 95% CI 0.002–0.211, p = 0.001) and shorter EFS (HR 6.318, 95% CI 2.659–15.012, p < 0.001). Conclusions Our findings suggest that KIT mutations are associated with poor response and shorter EFS in AML patients treated with VEN/HMA, highlighting the importance of KIT mutation status in risk stratification and treatment selection.